Neuroprotection in Glaucoma: Old and New Promising Treatments - Dario Rusciano; Salvatore Pezzino; Maria Giulia Mutolo; Rossella Giannotti; Aloisa Librando; Nicola Pescosolido (Advances in Pharmacological Sciences)
Glaucoma is a major global cause of blindness, but the molecular mechanisms responsible for the neurodegenerative damage are not clear. Undoubtedly, the high intraocular pressure (IOP) and the secondary ischemic and mechanical damage of the optic nerve have a crucial role in retinal ganglion cell (RGC) death. Several studies specifically analyzed the events that lead to nerve fiber layer thinning, showing the importance of both intra- and extracellular factors. In parallel, many neuroprotective substances have been tested for their efficacy and safety in hindering the negative effects that lead to RGC death. New formulations of these compounds, also suitable for chronic oral administration, are likely to be used in clinical practice in the future along with conventional therapies, in order to control the progression of the visual impairment due to primary open-angle glaucoma (POAG). This review illustrates some of these old and new promising agents for the adjuvant treatment of POAG, with particular emphasis on forskolin and melatonin.